Prescription writing through the lens of the threshold concept framework: a narrative review - Faraz Khurshid; Samra Bashir; Babu Noushad (Tabriz University of Medical Sciences, 2020)
Background: Although challenging, writing prescriptions is an essential practical competency of medical graduates. This process is transformative as it reflects medical students' ways of thinking and practising. A conceptual framework, similar to "way of thinking and practising", known as 'threshold concepts' can help students to establish meaningful connections between the transformative and conceptually difficult ideas underlying prescription writing. This enables them to think, practice and demonstrate the competence required for rational drug prescription conducive to effective pharmacotherapeutic care. Methods: A narrative review was conducted on a subset of articles retrieved during the course of an another literature review using four bibliographic databases from 15th August to 15th September 2019. The literature review is focussed on instructional interventions and their impact on university-level students learning pharmacology. Seminal papers on threshold concepts were also included to draw a comparison between prescription writing and key attributes of the threshold concepts framework. Results: An alignment supported by examples was observed between different aspects and challenges of prescription writing and key attributes of the threshold concept framework. Conclusion: Using the threshold concepts framework as a lens in prescription writing offers an insight to the curriculum designers employing it as a pedagogical utility in transforming medical students' way of thinking and practising for rational prescribing. Moreover, it also informs the likelihood of unidentified threshold concepts for beginners within the course of prescription writing.